Dimensions of aesthetic encounters perception, interpretation, and the signs of art - Innis, Robert E. (SUNY Series in American Philosophy and Cultural Thought Ser., 2022)
A novel fusing of multiple approaches and range of examples exploring the dimensions, objects, and import of aesthetic encounters.